Experimental Study on the Effects of Environmentally Friendly Composite Dust Suppressant on Soil Properties - Yong Xu; Min Liu; Ben Ma; Yingda Zhang; Zhuhong Liu; Zihao Liu (Applied Sciences)
This study aims to investigate the impact of a self-developed environmentally friendly composite dust suppressant on soil properties, with the objective of addressing dust pollution at construction sites. A series of experiments were conducted to examine the effects of the composite dust suppressant on soil strength (including compressive strength, shear strength, and surface hardness) and wind erosion resistance. The results demonstrate that spraying the soil with the composite dust suppressant diluted 10 times not only significantly enhances the compressive strength and ductility of the soil but also reduces the usage cost. Furthermore, the soil treated with the diluted suppressant exhibited the highest ultimate compressive strength after drying for seven days, which was 118.1 kPa higher than that of the undiluted treatment. The shear strength test also revealed a substantial increase in the shear strength of the soil treated with the dust suppressant under different vertical loads. Hardness tests showed that the composite dust suppressant containing binder significantly improved soil hardness. Wind erosion resistance tests further confirmed that the soil sprayed with the composite dust suppressant had a mass loss rate of only 9.36% within twenty minutes under an eleven-grade natural wind force, demonstrating good wind erosion resistance. This study not only provides a scientific basis for assessing the environmental impact of environmentally friendly composite dust suppressants on soil but also offers standardized evaluation techniques and experimental protocols for practical applications of dust suppressants.